Eco-coenotic analysis of pasture areas from the Danube Delta, Romania - Chirilă , Simona Dumitrița; Covaliov, Silviu; Răileanu , Ștefan; David , Livia Oana; Doroftei , Mihai; Burada , Adrian; Făgăraș , Marius (Hacquetia, 2024)
The study investigated the floristic composition of 12 pasture areas in the Danube Delta, and their neighbouring regions, and the relationships between the floristic composition and the environmental variables. The vegetation analysis was carried out based on the mean percentage values corresponding to the scale developed by the Braun-Blanquet. For the syntaxonomic assignment, 50 phytocoenological relevés were made. The relevés were analyzed using Agglomerative Hierarchical Clustering (flexible β algorithm and Bray-Curtis dissimilarity). The relationship between floristic composition and environmental variables was assessed using Detrended Correspondence Analysis (DCA) and Canonical Correlation Analysis (CCA) in CANOCO. Our results showed that the analyzed species are mostly mesoxerophilic, oligo-mesotrophic, and poorly exploited as fodder, with moderate tolerance to grazing and medium anthropogenic influence, predominantly urbanophobic. Numerical analysis identified eight well-defined communities, which correspond to associations described in the taxonomic literature, based on their diagnostic species. The predominant plant association is Hordeo murini-Cynodontetum dactyloni. The variation of the floristic composition is influenced by annual precipitation.